Analisis Keputusan Pembelian Rumah Tipe MBR Di Kabupaten Bantul, Yogyakarta - Khoirudin, Rifki (Lembaga Pengembangan Kinerja Dosen, 2022)
The MBR house is one of the government programs for low-income communities which is expected to help people have a decent place to live. Bantul Regency has the highest MBR housing construction in the Special Region of Yogyakarta Province. The purpose of this study was to determine the effect of price balance, payment system, location, environment, and promotion factors on purchasing decisions for MBR houses in Bantul Regency. The research was conducted in order to be optimally useful for consumers or developers of MBR houses. The study used primary and secondary data. The research sample used was 61 consumers of MBR houses in Bantul Regency. The method used is multiple linear regression. The results of the analysis show that of the five variables, there are only four variables that partially influence the decision to buy MBR houses in Bantul Regency, namely the price balance variable, payment system, environment, and promotion. Meanwhile, simultaneously all independent variables affect the decision to buy MBR houses in Bantul Regency. The results of the analysis of the adjusted coefficient of determination are known to be 67.1%.